KONSEP PENDIDIKAN ISLAM TENTANG MANUSIA DAN MEMULIAKAN MANUSIA - Nazaruddin (Jurnal Al-Karim : Jurnal Pendidikan, Psikologi dan Studi Islam, 2022)
Education is a system and a way to improve the quality of human life in all aspectsof human life. Education is the most important part of human life which also distinguisheshumans from animals. Therefore, there are various views which state that education is acultural process to elevate human "dignity and dignity" and lasts a lifetime. If so, theneducation plays a role that determines human existence and development, becauseeducation is an effort to preserve and transfer and transform cultural values in all itsaspects and types to the next generation to elevate human dignity. In fact, physical andpsychological differences are not a barrier and a gap that differentiates one human beingfrom another human being. Whoever he is and whatever his color, shape and background,he is completely the same before Allah SWT. Only what distinguishes it is submission andobedience (Taqwa) to Allah SWT. The existence of negative views or stigma againsthumans should not have happened, but in practice or in many events and incidents ineveryday life we often see, hear, witness abuses against humans themselves. Especially forpeople who have disabilities. This treatment is certainly unfair, because in the view ofAllah SWT as khaliq (creator), that humans are the same and have been given the samepotential as well. Humans are unique creatures, but behind their uniqueness human beingsare given a high position in world life.